Maxillary brown tumor associated with chronic kidney failure: a case report - Stênio Medeiros Queiroz; Rodrigo Gadelha Vasconcelos; Ana Luiza Dias Leite de Andrade; Adriana Gomes Amorim; Manuel Antonio Gordón-Nuñes; Roseana de Almeida Freitas; Hébel Cavalcanti Galvão (Sociedade Brasileira de Patologia Clínica, 2013)
The brown tumor is a bone lesion that may affect the entire skeleton, including the maxillary bones. These tumors are characterized as focal giant cell lesions that may be associated with primary or secondary hyperparathyroidism (HPT). Brown tumors are invasive in some cases and an association with chronic renal failure (CRF) has been reported. With the aim to facilitate the differential diagnosis of bone lesions that may affect dialysis patients, this paper describes a case of brown tumor in a 36- year old patient with CRF, secondary HPT carrier, who had a lesion on the right maxilla for approximately five months.